Association between serum globulin and cognitive impairment in older American adults - Huang, Jian; Li, Rong; Zhu, Hao; Huang, Dong; Li, Weiwang; Wang, Jing; Liu, Zhirong (Frontiers in Public Health, 2023)
Abstract Background and aims: Cognitive impairment is on the rise around the world, with profound economic and social consequences. Serum globulin, a marker of liver function, may also play a role in cognitive function. Unfortunately, no consistent conclusion exists regarding the association between serum globulin and cognitive function. Methods: Data from 2011 to 2014 National Health and Nutrition Examination Survey were used to assess the association between serum globulin and cognitive impairment. Cognitive function was assessed by three tests: Consortium to Establish a Registry for Alzheimer’s Disease (CERAD), Animal Fluency (AF), and Digit Symbol Substitution Test (DSST). Furthermore, the breakthrough point of cognitive impairment correlated with CERAD <5, AF <14, and DSST <34. A weighted multiple logistics regression model was used to verify the association between serum globulin and cognitive impairment. Generalized additive models (GAM) and a smooth curve fit (penalty spline method) to determine a non-linear relationship between serum globulin and cognitive impairment. Finally, subgroup analysis and interaction tests were conducted to further verify the association between serum globulin and cognitive impairment. Results: Data from 2768 participants aged ≥60 (in accordance with the study design) were collected for the final analysis. Data suggested that serum globulin levels were associated with an elevated of cognitive impairment based on the AF [full adjustment, OR = 1.05, 95% CI: 1.01-1.08] and DSST [full adjustment, OR = 1.06, 95% CI: 1.02-1.10] tests. Eventually, the GAM and smooth curve fit model were conducted to confirm that the association between serum globulin and cognitive impairment was non-linear. Moreover, the inflection point was 27 g/L serum globulin based on the CERAD test and the 35 g/L serum globulin based on the AF test. Finally, the interaction term between serum globulin and cognitive impairment based on the AF test indicated no significant interactions among all variables (all p for interaction >0.05). Conclusions: The association between serum globulin levels and cognitive impairment is non-linear. A threshold effect exists between serum globulin and cognitive impairment. Large-scale prospective clinical trials are needed to validate our findings.